2021
DOI: 10.1002/jcu.23026
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic predictors in chronic kidney disease: A hospital based case control study

Abstract: Background: Prevalence of Chronic Kidney Disease (CKD) is increasing globally with the concomitant upsurge in diabetes mellitus and hypertension. We explored the research question whether Ultrasonographic (US) renal parameters are potential predictors of CKD?Materials and methods: A case control study was conducted at a tertiary care hospital that included 50 confirmed cases of CKD and 100 nondiseased controls. Renal length, renal parenchymal thickness, and renal cortical thickness were measured in both cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been shown that a CKD management team combined with integrated community management can effectively improve renal function, delay disease progression and improve the quality of life in patients with CKD [7,8]. Several studies [9][10][11] have shown that integrated outpatientward-family management improves fear, depression, anxiety, and sleep disturbances in patients with mild cognitive impairment, hypertension, and stroke.…”
Section: Prefacementioning
confidence: 99%
“…It has been shown that a CKD management team combined with integrated community management can effectively improve renal function, delay disease progression and improve the quality of life in patients with CKD [7,8]. Several studies [9][10][11] have shown that integrated outpatientward-family management improves fear, depression, anxiety, and sleep disturbances in patients with mild cognitive impairment, hypertension, and stroke.…”
Section: Prefacementioning
confidence: 99%
“…These details aid in determining the extent of renal parenchymal injury and its reversibility (7), as well as the decision to undertake a renal biopsy (8). An aberrant sonographic finding was found in 67% of CKD cases, according to one inves ga on (9). Renal parenchymal disease refers to a group of disorders affec ng the renal cortex and medulla.…”
mentioning
confidence: 99%